Α-Glucosidase inhibitory phenylpropanoid-dihydrochalcone hybrids from the leaves of medicinal plant Malus hupehensis (Pamp.) Rehder. (December 2022) - Yuan, Lin-Lin; Shi, Bao-Bao; Feng, Tao; Huang, Rong; Li, Zheng-Hui; Chen, He-Ping; Liu, Ji-Kai
Abstract: Eight undescribed phenylpropanoid-dihydrochalcone hybrids, namely (+)- and (−)-malahupin A, (+)- and (−)-malahupin B, (±)-malahupin C, malahupinosides A and B, 7‴- epi -malahupinoside B, together with two known compounds, phloretin and phlorizin, were isolated from the leaves of the folk medicinal plant Malus hupehensis . Their structures were elucidated by extensive NMR and MS spectroscopic methods, chiral-phase analysis, and ECD calculations. Compounds (+)-malahupin B and malahupinoside B showed weak inhibition activities against the nitric oxide production in liposaccharide-induced murine RAW264.7 macrophages with IC50 values of 36.7 and 27.0 μM, respectively. Compounds (+)- and (−)-malahupin A, (+)- and (−)-malahupin B exhibited significant α-glucosidase inhibitory activity, with IC50 values of 22.5, 19.1, 19.2, and 17.4 μM, respectively. The postulated biosynthetic pathways to these hybrid compounds were proposed. This work represents the first report of the natural phenylpropanoid-dihydrochalcone hybrid compound, and lays foundation for the study on the bioactive principles of the ethnic hypoglycemic medicinal plant. Graphical abstract: Natural chalcone-phenylpropanoid hybrids with anti-nitro oxide activity from Malus hupehensis . Image 1 Highlights: Phenylpropanoid-dihydrochalcone hybrids were isolated from the medicinal plant Malus hupehensis . The absolute configurations of all the isolates were determined. Four compounds showed significant α-glucosidase activity.